Accessing Energy Security of BRICs Nations for Strategic Partnership - Varghese, Varun; Pai, Anil M (International Journal of Advanced Research in Engineering; Vol 2 No 2 (2016): International Journal of Advanced Research in Engineering, 2016)
Availability of the energy is crucial for the sustenance of any country. The energy available at a countries disposal is dependent on a lot of factors such as the geographical location, technology and resources available for the energy extraction, Government policies, international alliances, military might etc. Developed countries, already having an energy intensive lifestyle are supposedly shifting to greener ways whereas in the new emerging world the people have an aspiration to lead an energy rich materialistic lifestyle. Within this chaos, the security of the bare minimum energy needed for the survival of every individual is at stake. A small crisis due to political, environmental or military may put the population of that nation in jeopardy. Thus Energy security is essential for countries sustenance and securing energy through strategic ties with likeminded countries becomes crucial. This paper tries to highlight the energy requirement and potential of the emerging economies and also tries to identify the challenges posing them. The paper discusses the opportunity for strategic partnership, for energy, within the BRIC Nations and suggests interventions and policies to increase the collective energy security (pertaining to certain sectors) of these nations.